The integration of Shariah compliance in information system of Islamic financial institutions: Qualitative evidence of Malaysia - Ayedh A.M.; Mahyudin W.A.; Abdul Samat M.S.; Muhamad Isa H.H. (Emerald Group Publishing Ltd., 2024)
Indexed by Scopus/ERA